PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) DENGAN PEMBERIAN TRICHOKOMPOS JERAMI PADI DAN KALIUM DI LAHAN GAMBUT - Azman Azman; Hapsoh Hapsoh; Fifi Puspita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The cultivation of red onion in peatlands have several problems that have low pH, highcation exchange capacity, low base saturation and low content of macro and micro nutrients. Efforts to solve the problem on peat soil should be giving rice straw Trichokompos and Potassium fertilizer as it can improve the physical, biological and chemical on peat soil. The purpose of this study was to determine the effect of interaction between rice straw Trichocompost and Potassium, the influence of rice straw Trichocompost factors and the influence of Potassium factors, as well as getting the best combination on the growth and red onion production on peatlands. This research was conducted experimentally, using a randomized block design (RBD) factorial consisting of two factors and three replications, namely: rice straw Trichokompos factor (0, 250, 500, 750 g / plot) and Potassium factor (0, 2.5, 5, 7.5 g KCL / plot). Observational data obtained were analyzed using variance analysis and conducted a further test using Duncan's New Multiple Range Test (DNMRT) at 5% level. The results of the study showed that giving rice straw Trichocompost and potassium fertilizers, indirectly affects growth and onion production. Provision of rice straw Trichocompost 250 g / plot (10 ton / ha) and potassium fertilizers KCl 5 g / plot (200 kg / ha) has the best ability to increase growth and onion production. Keywords: Onion, peat, rice straw Trichocompost, Potassium